Physiological monitoring to prevent diving disorders - Beatty, Paul; Evans, William; Gravelyn, Sara; Tumperi, Marshall; Daubon, Druso; Veith, Austin (Frontiers in Physiology, 2024)
Insight into human physiology is key to maintaining diver safety in underwater operational environments. Numerous hazardous physiological phenomena can occur during the descent, the time at depth, the ascent, and the hours after a dive that can have enduring consequences. While safety measures and strict adherence to dive protocols make these events uncommon, diving disorders still occur, often with insufficient understanding of the factors that triggered the event. This review first examines the most common diving disorders and their incidence rates across recreational and US military dive activities. The review then identifies physiological biomarkers (e.g., heart rate, heart rate variability, blood pressure, respiration rate, temperature, oxygen saturation) that may provide a holistic view of the diver’s current physiological state and potentially detect the most concerning diving disorders (e.g., decompression illnesses, gas mixture-related disorders, barotraumas, and environment exposure). Although considerable research is still needed to verify the use of these biometrics in the diving environment, the research described in this review presents a promising path to developing a system that can detect pending diving disorders and provide divers and other necessary parties with an early warning before mishaps occur.